A note on the trace theorem for Besov-type spaces of generalized smoothness on d-sets - Wagner, Vanja (Array, 2019)
The main goal of this paper is to give a complete proof of the trace theorem for Besov-type spaces of generalized smoothness associated with complete Bernstein functions satisfying certain scaling conditions on d-sets D⊂ℝn, d≤ n. The proof closely follows the classical approach by Jonsson, Wallin in [18] and the trace theorem for classical Besov spaces. Here, the trace space is defined by means of differences. When d=n, as an application of the trace theorem, we give a condition under which the test functions Cc∞(D) are dense in the trace space on D.